Investigating distance halo effect of fixed automated speed camera based on taxi GPS trajectory data - Chuanyun Fu; Hua Liu (Journal of Traffic and Transportation Engineering (English ed. Online), 2023)
Background: The deterrence effect of automated speed camera (ASC) is still inconclusive. Moreover, it is pointed out that ASC may have varying deterrence effects on different types of road users (e.g., taxis). Objective: This study intends to investigate the distance halo effect of fixed ASC (hereafter called ASC) on taxis. Method: More than 1.34 million taxis' GPS trajectory data were collected. A novel indicator, the delta speed (defined as the difference between the traveling speed and the speed limit), was proposed to continuously describe the variations in traveling speeds. The upstream and downstream critical delta speeds during each time period on weekdays and weekends were obtained by using K-means clustering method, respectively. Based on the critical delta speeds, the ranges of upstream and downstream distance halo effects of ASC during different time periods on weekdays and weekends were determined separately and compared. Results: The downstream critical delta speed is smaller than the upstream one. The upstream and downstream distance halo effects of ASC on taxis are within a range of 8–2180 m and an area of 10–580 m to the ASC location, respectively. There are no obvious difference in the ranges of upstream and downstream distance halo effects of ASC on taxis between different time periods or between weekdays and weekends. Conclusion: The present study confirms that the upstream and downstream distance halo effects of ASC on taxis have different ranges and the stabilities of time-of-day and day-of-week. Practical application: The findings of this study can provide a basic reference for reasonably deploying ASCs within a region.